الدرس العقدي المدرسي في سياق أسئلة تجديد النقل الديداكتيكي؛ معالم وضوابط - عمر بن سكا (Namaa Magazine, 2024)
This research aims to reveal aspects of the debates that arise in the context of discussing the subject of the didactic transposition of Islamic knowledge and concepts, especially what is related to the school doctrinal lesson. That is, considering the issues and requirements for transforming and transferring knowledge at the level of teaching and learning, or in the classroom practices, and what this requires of seeking to control the parameters of renewing the concept of didactic transposition at this level. In addition, we try to provide some methodological proposals and approaches that contribute to revealing the most effective way to deal with the programs... About the most prominent findings of the research, we can say generally that research into the form of educational practices and the nature of the interactions that govern the relation between (teacher-student) is extremely important for understanding the transformations that knowledge undergoes in which both parties of the educational process are a pivotal part, for there exist the true curriculum. Which is not devoid of the fingerprints and stakes of the actors in the teaching and learning process. Finally, the research suggested making the focus of innovation in the doctrinal lesson revolve around: realism, intellectual education, and an optimal application of the requirements of didactic transmission as a process of interaction and continuous guidance of the learning act, where its subject is knowledge.